Increasing Students' Activity and Understanding of Concepts in Mathematics Learning Using Lesson Study-Based PBL - Puspitaningrum Ayu Rahmadhani; Isna Farahsanti; Edi Ariyanto (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
This research is motivated by the lack of student learning activity that affects the understanding of student concepts in mathematics learning in class XI F 4.2 SMA Veteran 1 Sukoharjo. The importance of student activity in learning needs to be done so that learning becomes interesting and students have the curiosity to learn more deeply related to the knowledge taught by the teacher, in addition, understanding the concept is one of the important factors that supports student activity in the learning process. This study aims to improve the activity and understanding of student concepts in mathematics learning using PBL based on lesson study. The subjects in this study were 27 students of class XI F4.2 majoring in social sciences. The study results showed that using the PBL learning model based on lesson study can improve the activity and understanding of student concepts in learning. Based on the study's results, the percentage of student activity increased from pre-cycle 15% and cycle 1 by 59% then cycle 2 by 100%. This is the same as the increase in student's conceptual understanding from the pre-cycle stage with a percentage of 37%, then cycle 1 by 59% to cycle 2 by 100%, so it can be concluded that using the lesson study-based PBL learning model can increase students' activeness and conceptual understanding.